2009
DOI: 10.1111/j.1420-9101.2009.01741.x
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion‐based approach to stochastic individual growth and energy budget, with consequences to life‐history optimization and population dynamics

Abstract: Using diffusion processes, I model stochastic individual growth, given exogenous hazards and starvation risk. By maximizing survival to final size, optimal life histories (e.g. switching size for habitat/dietary shift) are determined by two ratios: mean growth rate over growth variance (diffusion coefficient) and mortality rate over mean growth rate; all are size dependent. For example, switching size decreases with either ratio, if both are positive. I provide examples and compare with previous work on risk‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…This upper threshold depends on the structural size already constructed (i.e., on z(t)), therefore, it defines a curve in the z-y coordinate space. Following my previous work (Filin, 2009), I hereafter refer to this curve as the singular arc, denoted by _ yðzÞ. The singular arc represents the optimal strategy for investment in (irreversible) structural growth, or an optimal rule for dividing total body mass between reversible reserves, y, and irreversible structure, z, as the organism grows (Filin, 2009).…”
Section: Basic Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This upper threshold depends on the structural size already constructed (i.e., on z(t)), therefore, it defines a curve in the z-y coordinate space. Following my previous work (Filin, 2009), I hereafter refer to this curve as the singular arc, denoted by _ yðzÞ. The singular arc represents the optimal strategy for investment in (irreversible) structural growth, or an optimal rule for dividing total body mass between reversible reserves, y, and irreversible structure, z, as the organism grows (Filin, 2009).…”
Section: Basic Definitionsmentioning
confidence: 99%
“…Following much recent modeling of individual growth (Kooijman et al, 1999;Kooijman, 2010;Müller and Nisbet, 2000;Filin, 2009Filin, , 2010, I divide the total body mass of an individual into a reversibly changing component (hereafter, reserves; denoted by y) and an irreversibly growing component (hereafter, structure; z). Therefore, organismal size is defined by a pair of values (y,z).…”
Section: Basic Definitionsmentioning
confidence: 99%
“…In this study, I extended my previous work (Filin, 2009) and considered optimal 254 stopping conditions for structural growth, when individuals must grow to some given finite 255 target size, and when reproduction is included in the optimization objective. I found that even 256 when the optimization objective is maximizing survival to target size (as in Filin, 2009; i.e., 257 no reproduction) it is optimal to abandon structural growth altogether close to the target size, 258 and to proceed only by accumulating reserves.…”
Section: Discussion 253mentioning
confidence: 99%
“…I found that even 256 when the optimization objective is maximizing survival to target size (as in Filin, 2009; i.e., 257 no reproduction) it is optimal to abandon structural growth altogether close to the target size, 258 and to proceed only by accumulating reserves. 259…”
Section: Discussion 253mentioning
confidence: 99%
See 1 more Smart Citation